The Secret of Toni - Seawell, Molly Elliot, 1860-1916; Brehm, George, 1878-1966 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Secret of Toni" by Molly Elliot Seawell is a novel written in the early 20th century. The story takes place in a sunny garrison town in southern France and focuses on the life of a young boy named Toni Marcel, who is characterized by his adventurous spirit and playful nature. The narrative likely revolves around Toni's relationships with his friends, his mother, and his aspirations, infused with elements of childhood innocence and exploration. At the start of the novel, we are introduced to Toni's vibrant world, where he navigates his interactions with friends, his mother's candy shop, and the local garrison filled with soldiers. Toni is portrayed as a clever yet mischievous boy who prefers daydreaming about adventures and horses over attending school. His friendships with Paul, a more responsible boy, and Jacques, a tin soldier, shape his experiences and insights. The opening chapters set the stage for Toni$1 (Bs ambitions and youthful romantic notions regarding his ideal marriage with Denise, the pretty daughter of the local baker, as he seeks to balance the joy of childhood with the realities of growing up. (This is an automatically generated summary.)s
Release date is 2021-12-20
D A Alexander and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Friendship -- Fiction; France -- Fiction; Man-woman relationships -- Fiction